An Exploration students' motivations in improving their English skill: Karawang Junior Islamic Boarding School Case - Indana Zulfa; Maman Suryaman (Eduvelop: Journal of English Education and Development, 2022)
One of the important factors in supporting the achievement of the following characteristics of successful learning in English is motivation in learning English. The definition of motivation itself is the combined effect of effort and a desire to accomplish the goal. However, Indonesia that has a lot of diversity is not easy in realizing equal learning success in each region. The diversity of learning systems in Indonesia is also one of the interesting things to study. One of the researchers' concerns in this study is the learning system in Islamic boarding schools. In order that, tThis study aims at Exploring Secondary Students’ Motivation in Accomplish Successful English Language Learning. The student's behaviour, cognitive, and emotional will be carefully investigated. As this research concerns on students' motivations, this research tends to use a research case study at junior high school students. A qualitative method trough questionnaire is used in this research. The result shows that students' interest in learning English in schools based on Islamic boarding schools is not too high, because it is proven in the next question which shows results that most students find it difficult to learn English. It is also proven that they feel that the environment in which they live, in other words, the pesantren has not been able to increase their students' interest in learning English. Teachers must be able to become facilitators to increase students' interest in learning English